2022
DOI: 10.24114/ijcst.v5i2.37465
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Levels from Various Types of Coffee Drink Packaging Circulated in the Medan City Market Were Examined Using a UV Spectrophotometry Method

Abstract: Coffee drinks are drinks that come from the processing and extraction of coffee beans. One of which is caffeine. Coffee contains approximately 24 of the most important substances. The purpose of this study was to determine the level of caffeine in coffee drinks from various types of packaging. The research stages include sample collection and preparation; identification of caffeine content; and examination of caffeine levels using UV spectrophotometry. The results showed that the three samples of coffee drinks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Spektrofotometer terdiri atas spektrometer dan fotometer. Spektrofotometer menghasilkan sinar dari spektrum dengan panjang gelombang tertentu dan fotometer adalah alat pengukur intensitas cahaya yang ditransmisikan atau yang diabsorpsi (Dalimunthe et al, 2022). Spektrofotometer tersusun atas sumber spektrum tampak yang kontinyu, monokromator, sel pengabsorbsi untuk larutan sampel atau blangko dan suatu alat untuk mengukur perbedaan absorbsi antara sampel dan blangko ataupun pembanding.Pelarut yang biasa digunakan dalam daerah-daerah ultraviolet dan terlihat ialah: aseton, benzena, karbon tetraklorida, kloroform, dioksan, diklorometan, etanol Pelarut-pelarut yang digunakan dalam spektrofotometri harus melarutkan cuplikan dan meneruskan radiasi dalam panjang gelombang yang sedang dipelajari (Noviyanto, 2020).…”
Section: Pendahuluanunclassified
“…Spektrofotometer terdiri atas spektrometer dan fotometer. Spektrofotometer menghasilkan sinar dari spektrum dengan panjang gelombang tertentu dan fotometer adalah alat pengukur intensitas cahaya yang ditransmisikan atau yang diabsorpsi (Dalimunthe et al, 2022). Spektrofotometer tersusun atas sumber spektrum tampak yang kontinyu, monokromator, sel pengabsorbsi untuk larutan sampel atau blangko dan suatu alat untuk mengukur perbedaan absorbsi antara sampel dan blangko ataupun pembanding.Pelarut yang biasa digunakan dalam daerah-daerah ultraviolet dan terlihat ialah: aseton, benzena, karbon tetraklorida, kloroform, dioksan, diklorometan, etanol Pelarut-pelarut yang digunakan dalam spektrofotometri harus melarutkan cuplikan dan meneruskan radiasi dalam panjang gelombang yang sedang dipelajari (Noviyanto, 2020).…”
Section: Pendahuluanunclassified
“…This technique revealed that the cold and hot brew coffee samples exhibited a green color change, consistent with the caffeine standard. In using the Parry method, a positive shift to green was observed, indicative of the formation of a cobalt-caffeine complex compound (Figure 1) [30] [31]. The cobalt ion in the Parry reagent is positively charged, enabling it to bond with the nitrogen group found in the caffeine molecule [32].…”
Section: Identification Of Caffeinementioning
confidence: 99%